A meta‐analytic review of the Self‐Administered Interview©: Quantity and accuracy of details reported on initial and subsequent retrieval attempts. Issue 2 (5th November 2020) - Horry, Ruth; Hughes, Chelsea; Sharma, Anagha; Gabbert, Fiona; Hope, Lorraine
Abstract: The Self‐Administered Interview (SAI©) is designed to elicit detailed witness reports in the aftermath of incidents. In two sets of meta‐analyses, we compared the number of correct details reported, the number of incorrect details reported, and the accuracy of reports provided by witnesses in initial reports (SAI© vs. other reporting formats) and in subsequent accounts (initial SAI© vs. no initial SAI©). The number of comparisons ranged from 15 to 19, ( N = 722 to 977). For initial accounts, the SAI© was associated with more correct details and more incorrect details than other reporting formats; accuracy was slightly lower for the SAI© than for other reporting formats. Subsequent accounts were more detailed and accurate for witnesses who had completed an initial SAI© than for those who had not. The SAI© is an effective tool for capturing detailed initial accounts and for preserving witness memory until a formal interview can be conducted.